Language Shift and Maintenance of Mina Yeisa in Seram Migrant Communities, Manokwari, West Papua - Fadli Rumagia; Hugo Warami; Handrini Ardiyanti; Fanny Henry Tondo (LPPM Sekolah Tinggi Ilmu Ekonomi 45 Mataram, 2026)
Language serves as both a communicative resource and a marker of cultural identity. In migrant contexts, minority languages are often subject to pressure from dominant languages, leading to language shift. This study examines the shift and maintenance of the Mina Yeisa dialect of Eastern Seram language among Seram migrant communities in Manokwari, West Papua. Using a qualitative descriptive approach, data were collected through in-depth interviews, participant observation, conversational analysis, Swadesh list elicitation, documentation, and visual ethnography. The analysis is informed by Ethnolinguistic Vitality Theory. The findings reveal a pronounced intergenerational shift toward dominant languages in public and educational domains, while Mina Yeisa is maintained primarily in familial interactions. Language shift is driven by socio-economic mobility, majority language dominance, and limited institutional support, whereas language attitudes and community cohesion support maintenance. The study proposes a community-based model for sustaining minority languages in multilingual settings.